ENHANCING STUDENTS’ PUBLIC SPEAKING PERFORMANCE THROUGH AI-ASSISTED REFLECTIVE DIALOGUE IN HIGHER EDUCATION - Iswadara Kharisma Doa (Universitas Wijaya Kusuma Surabaya, 2025)
Public speaking is a fundamental competence in higher education; however, many students continue to experience persistent challenges related to confidence, organization, and feedback quality. This study aims to examine the effectiveness of AI-assisted reflective dialogue in enhancing students’ public speaking performance in higher education. A mixed-methods design was employed, involving AI-assisted reflective dialogue sessions, performance-based speaking assessments, and students’ reflective responses. The findings indicate notable improvements in students’ public speaking performance, particularly in confidence, delivery, organization, and metacognitive awareness. Despite the growing literature on public speaking pedagogy and AI-enhanced learning, empirical research examining AI-assisted reflective dialogue as a systematic formative feedback mechanism in higher education remains limited. This study addresses this gap by reconceptualizing AI as a dialogic reflective partner that supports reflective learning and self-regulated public speaking development. In conclusion, AI-assisted reflective dialogue offers a pedagogically meaningful approach to enhancing communicative competence and reflective learning in higher education.